2017
DOI: 10.1159/000484344
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis in Children on Chronic Peritoneal Dialysis: The Experience of a Large National Pediatric Cohort

Abstract: Background: We performed this study to evaluate the incidence, risk factors, microbiology, treatment, and outcome of peritonitis in pediatric Peritoneal dialysis (PD) patients at a nationwide prospective study. Methodology: Patients younger than 18 years recruited in the BRAZPD II study from 2004 to 2011, who presented their first peritonitis episode, were included in the study. Results: We found 125 first episodes of peritonitis in 491 children PD patients (0.43 episodes/patient-year). Patients free of perito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 31 publications
7
14
5
Order By: Relevance
“…The ratio of peritonitis in our study was lower than others because our time of follow-up was shorter than other studies. There was 27.3% patient with positive bacteria culture in our study, that similar to other study results [5,19].…”
Section: Prevalence Peritonitissupporting
confidence: 92%
See 1 more Smart Citation
“…The ratio of peritonitis in our study was lower than others because our time of follow-up was shorter than other studies. There was 27.3% patient with positive bacteria culture in our study, that similar to other study results [5,19].…”
Section: Prevalence Peritonitissupporting
confidence: 92%
“…Gadola L. et al [18] surveyed the rate of peritonitis in 222 PD patients following-up 6 years, the result showed 95 patients suffered 1 or more episodes of peritonitis (42.79%). In children, the ratio of peritonitis was 25.45% in Ponce's study with 7 years follow-up (125 rst episodes of peritonitis in 491 children PD patients) [19]. The ratio of peritonitis in our study was lower than others because our time of follow-up was shorter than other studies.…”
Section: Prevalence Peritonitiscontrasting
confidence: 64%
“…The ratio of peritonitis in our study was lower than others because our time of follow-up was shorter than other studies. There was 27.3% patient with positive bacteria culture in our study, that similar to other study results [5,20].…”
Section: Prevalence Peritonitissupporting
confidence: 92%
“…[11], where no variation was noted in the peritonitis rates among children. According to our study and their study, the peritonitis rate among Saudi children on PD appears higher than that reported in other countries [1,[4][5][6] where they met ISPD recommendations. There is a need for an urgent intervention program to reduce and prevent peritonitis in our center.…”
Section: Resultscontrasting
confidence: 57%